2019
DOI: 10.3390/app9132652
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Advanced Oxidation Processes for Sulfamethoxazole Degradation

Abstract: The degradation of sulfamethoxazole (SMX) by several advanced oxidation processes (AOPs) is carried out in the presence of different catalysts. The catalysts used consisted of carbon nanotubes (CNT), titanium dioxide (TiO2), a composite of carbon nanotubes and titanium dioxide (TiO2/CNT), and iron supported on carbon nanotubes (Fe/CNT). SMX removal was evaluated by catalytic ozonation, photocatalysis, catalytic oxidation with hydrogen peroxide, and combinations of these processes. The evolution of the SMX conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Furthermore, the ON storages were also much higher in the invaded habitats than in the normal habitats (Table 2). However, the invasion of S. alterniflora and Lythrum salicaria dramatically stimulated N mineralization and nitrification, by adding N input, thus the storage of ON was unchanged [50][51][52]. Therefore, this study demonstrated that alligator weed invasion could be beneficial to the net storage of N fractions.…”
Section: Organic Matter In the Wetland Habitatsmentioning
confidence: 68%
“…Furthermore, the ON storages were also much higher in the invaded habitats than in the normal habitats (Table 2). However, the invasion of S. alterniflora and Lythrum salicaria dramatically stimulated N mineralization and nitrification, by adding N input, thus the storage of ON was unchanged [50][51][52]. Therefore, this study demonstrated that alligator weed invasion could be beneficial to the net storage of N fractions.…”
Section: Organic Matter In the Wetland Habitatsmentioning
confidence: 68%
“…In addition, the cost of AO is high, and the intermediate degradation products are difficult to be completely oxidized. In view of this, the combination of a variety of treatment processes to improve the treatment effect of pollutants has gradually become the focus of current research (Huang et al, 2019;Jourshabani, Dominic, Achari, & Shariatinia, 2019;Martini, Orge, Faria, Pereira, & Soares, 2019;Wu, Zhou, Lu, Zhou, & Shen, 2019). Hylling et al (2019) reported a method to remove micropollutants in drinking water by combining RO filtration with biodegradation.…”
Section: Combinations Of Treatment Technologiesmentioning
confidence: 99%
“…Such conditions enhance organophosphate pesticides degradation through advanced oxidation processes [37]. The H2O2 oxidation generates •OH, and in turn releases hydronium ions, The differences between malathion and TOC removal behavior is related to the degradation of pesticide to less complex organic molecules, in terms of chemical structure, but together contributes to the same organic carbon concentration [31]. Regarding TOC removal, it is only observed if the degradation product is CO 2 , equivalent to mineralization.…”
Section: Behavior Of Physicochemical Parametersmentioning
confidence: 99%